1999
DOI: 10.1021/la9900831
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Receding Contact Angle of Sessile Drops on Polymer Surfaces by Evaporation

Abstract: The receding contact angles of water drops on PMMA and PET surfaces were determined by using video microscopy to follow the time-dependent evaporation of sessile drops. Depending on the initial drop size, receding angles of θr = 54−64° for PMMA and θr = 64−66° for PET were found with an average hysteresis of 23.5 ± 1.5 and 19.5 ± 1.5°, respectively. Advancing and receding angles, θa and θr, were also determined by the needle-syringe and the inclined plane methods for comparison. The discrepancies from the mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
147
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 188 publications
(160 citation statements)
references
References 59 publications
11
147
0
Order By: Relevance
“…In addition, we measured both advancing (Â adv ) and receding (Â rec ) water contact angles (WCA) on the sample surfaces by increasing the volume of the droplets from 3 to 8 L and decreasing from 8 to 4 L respectively through the needle by using the automatic dispenser while the needle was kept within the liquid droplet. Â rec were also measured by drop evaporation method for better precision [43,44].…”
Section: Contact Angle Measurementmentioning
confidence: 99%
“…In addition, we measured both advancing (Â adv ) and receding (Â rec ) water contact angles (WCA) on the sample surfaces by increasing the volume of the droplets from 3 to 8 L and decreasing from 8 to 4 L respectively through the needle by using the automatic dispenser while the needle was kept within the liquid droplet. Â rec were also measured by drop evaporation method for better precision [43,44].…”
Section: Contact Angle Measurementmentioning
confidence: 99%
“…30 The precise measurement of receding contact angles is a difficult process and r can be determined by following the time dependent drop evaporation measurements with a videomicroscopy technique in comparison with the static needlesyringe sessile drop method. 31,32 Contact angle hysteresis, CAH, is defined as the difference between the advancing and receding contact angles, CAHϵ a − r . This hysteresis is due to the system under investigation not meeting the ideal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…(2.18) and (2.20) are validated against available experimental data extracted from literature sources [5,7,45]. The characteristic time of the process can be calculated using Eq.…”
Section: Validation Against Experimental Datamentioning
confidence: 99%
“…Water on PET [45] Theory (θ ad =1.486; t ch =760 s) Figure 8. glass, the estimation showed that the average temperature of the droplet surface, T av , appeared to be higher than the ambient temperature, T ∞ , what is in contradiction with the physics of the phenomenon.…”
Section: Validation Against Experimental Datamentioning
confidence: 99%
See 1 more Smart Citation